Effect of Various Methods of Processing Curly Red Chilli (Capsicum annum L.) on the Physicochemical and Organoleptic Characteristics of Coconut Nira Soy Sauce - Muhammad Rizky Ramanda; Alexandra T. Putri; Amalia Wahyuningtyas (UNIVED Press, Dehasen University Bengkulu, 2023)
Soy sauce is a liquid product derived from fermented soybeans or soybean meal plus sugar with or without the addition of other food ingredients. Soy sauce is usually made from soybeans, but apart from soybeans, soy sauce can be made with coconut sap. Previously, research on coconut sap soy sauce had been conducted, but the results showed that the panelists' preference for coconut sap soy sauce was still low. In this study, the addition of curly red chili with various processing methods and spices was thought to increase the panelists' preference for coconut sap soy sauce. This study aimed to examine the physicochemical and organoleptic characteristics of coconut sap soy sauce with the addition of curly red chili with four processing methods. The chili processing methods used were coarsely ground chilies, finely ground chilies, dried chili powder, and chili extracts. The research stages include the process of making coconut sap soy sauce, organoleptic tests, viscosity tests, acidity tests (pH), and sucrose tests. ANOVA (Analysis of Variance) and SPSS applications were used to analyze the test data. If significant results are obtained, the analysis is continued with Duncan's Multiple Range Test (DMRT) with a significance level of 5%. Based on the test results, the addition of various chili processing methods significantly affected the degree of acidity (pH), viscosity, sucrose content, hedonic color, hedonic viscosity, and hedonic spiciness. However, the effect is not significant on the hedonic aroma. The coconut sap soy sauce with chili extract obtained the highest score for the ranking test assessment.